PERANCANGAN SISTEM INFORMASI JASA PENGIRIMAN BARANG ANTAR PULAU MENGGUNAKAN WATERFALL PADA PT. SINAR WIJAYA KUSUMA JAKARTA - DWI YUNI UTAMI (LPPM Universitas Bina Sarana Informatika, 2015)
PT Sinar Wijaya Kusuma is one of the companies in Pondok Gede, which is engaged in the delivery of goods (Expeditionary), which all data processing is still manually. This causes difficulties in collecting data, especially the data container incoming and outgoing because quite a lot and presentation of the required information also becomes ineffective and inefficient, even sometimes the data can not be found, causing redundancy of data when the missing data in the record again. Consequently reports required by marketing managers often can not be available when needed in solving a problem that occurs in the company, the authors intend to try to handle the processing of data on PT Sinar Wijaya Kusuma and designing an information system delivery. Data collection was performed by the method of literature review, interviews, and observation. The method of system development information system using the waterfall method, whereas the data flow method used is a structured method, DFD (Data Flow Diagram) in depicting functional model and ERD (Entity Relationship Diagram) to describe the data model. This information system is built using Visual Basic software with microsoft access storage media.